2021
DOI: 10.1016/j.ajog.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Placenta Accreta Spectrum Treatment With Intraoperative Multivessel Embolization: the PASTIME protocol

Abstract: This study was presented at the 41st annual pregnancy meeting of the Society for Maternal-Fetal Medicine, held virtually, January 25e30, 2021.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…There are several approaches available to decrease surgical blood loss during cesarean hysterectomy, including multivessel surgical ligation, temporary aortic clamping, multivessel embolization, and balloon occlusion of the aorta or iliac arteries. 3 Several groups have reported superior outcomes with resuscitative endovascular balloon occlusion of the aorta (REBOA) as an adjunct to hemorrhage control during cesarean hysterectomy for PAS. [4][5][6][7][8][9][10][11][12] A meta-analysis of 731 PAS patients who underwent cesarean deliveries in which a REBOA catheter was used to occlude the infrarenal aorta, termed zone 3, found that these women experienced significantly less blood loss, received fewer transfusions, and achieved a higher rate of uterine preservation compared with other hemorrhage control strategies.…”
Section: Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several approaches available to decrease surgical blood loss during cesarean hysterectomy, including multivessel surgical ligation, temporary aortic clamping, multivessel embolization, and balloon occlusion of the aorta or iliac arteries. 3 Several groups have reported superior outcomes with resuscitative endovascular balloon occlusion of the aorta (REBOA) as an adjunct to hemorrhage control during cesarean hysterectomy for PAS. [4][5][6][7][8][9][10][11][12] A meta-analysis of 731 PAS patients who underwent cesarean deliveries in which a REBOA catheter was used to occlude the infrarenal aorta, termed zone 3, found that these women experienced significantly less blood loss, received fewer transfusions, and achieved a higher rate of uterine preservation compared with other hemorrhage control strategies.…”
Section: Questionsmentioning
confidence: 99%
“…There are several approaches available to decrease surgical blood loss during cesarean hysterectomy, including multivessel surgical ligation, temporary aortic clamping, multivessel embolization, and balloon occlusion of the aorta or iliac arteries 3 . Several groups have reported superior outcomes with resuscitative endovascular balloon occlusion of the aorta (REBOA) as an adjunct to hemorrhage control during cesarean hysterectomy for PAS 4–12 .…”
mentioning
confidence: 99%
“…According to the SMFM guidelines, the role of iliac artery occlusion (internal and common arteries) is still controversial as it has been reported to decrease blood loss in some studies but showed no difference in others [2]. It also has been postulated that PAS is associated with neovascularisation and abnormal blood supply therefore occluding pelvic vessels may exacerbate bleeding from the collateral circulation, thus limiting the benefit of this procedure [17][18][19][20][21][22][23][24][25][26]. International Federation of Obstetrics and Gynecology (FIGO) does not recommend its routine use due to a lack of strong supporting evidence of their benefit [1].…”
Section: Discussionmentioning
confidence: 99%
“…average blood loss while drastically reducing the potential for nontarget ischemia that can result from aortic or internal iliac balloon occlusion. 86,108 Similar to most balloon occlusion data, prophylactic embolization data are retrospective, but the reported reduction in blood loss and transfusion rates sparks interest for a prospective study.…”
Section: Prophylactic Multivessel Embolizationmentioning
confidence: 98%